Neodymium (Nd) isotope composition of fossil fish debris and mixed planktic foraminifera at IODP Site 383-U1540 during Marine Isotope Stage 11 - Jebasinski, Lena; Frick, Daniel A; Kapuge, Aruggoda K I U; Basak, Chandranath; Saavedra-Pellitero, Mariem; Winckler, Gisela; Lamy, Frank; Gottschalk, Julia (In: Jebasinski, L et al. (2025): Stable oxygen isotope and trace element ratios, neodymium isotope composition, sedimentary census counts and opal content at IODP Site 383-U1540 during Marine Isotope Stage 11 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974158, 2025)
This dataset presents neodymium (Nd) isotope ratios derived from fossil fish teeth/-bones (hereafter fish debris) and Fe-Mn coatings from mixed planktic foraminifera covering Marine Isotope Stage 11 at International Ocean Discovery Program Site U1540 (55° 8.47ʹ S, 114° 50.52ʹ W, 3580 m). The measured 143Nd/144Nd ratios have been corrected using a reference value of 143Nd/144Nd = 0.7219 and an exponential mass fractionation law, and were normalized to the international standard JNdi-1 (143Nd/144Nd = 0.512115; Tanaka et al., 2000). The Nd isotope results are reported in ε-notation (εNd), which represents the deviation in parts per 10,000 from the Chondritic Uniform Reservoir (CHUR), where 143Nd/144Nd = 0.512638 (Jacobsen & Wasserburg, 1980). Both internal (2SE) and external (2σ) errors are reported. All samples were bracketed by JNdi-1 and the reported external errors reflect the reproducibility (2σ) of the JNdi-1 standards analyzed alongside the samples. The samples were prepared for analyses and measured for Nd concentration using a Thermo Fisher triple quadrupol iCAP inductively coupled plasma-mass spectrometer (ICP-MS) at the University of Delaware (Newark, DE, USA) and measured for Nd isotopes at Pennsylvania State University (University Park, PA, USA) using a Thermo Fischer Scientific Neptune Plus Multi Collector ICP-MS.
Keywords: Bottom water oxygen; Bottom water temperature; Circumpolar deep water; Foraminiferal geochemistry; South Pacific Ocean